2017
DOI: 10.18632/oncotarget.18555
|View full text |Cite
|
Sign up to set email alerts
|

Role of the JAK2/STAT3 signaling pathway in the pathogenesis of type 2 diabetes mellitus with macrovascular complications

Abstract: This study investigated the role of the JAK2/STAT3/SOCS pathway in type 2 diabetes mellitus (T2DM) and macrovascular complications (DV) (T2DM+DV) conditions. Human umbilical vein endothelial cells (HUVECs) were co-cultured with human monocytes (THP-1) and exposed to peripheral blood sera from 30 T2DM patients, 30 patients with T2DM+DV and 30 healthy controls; the groups were divided into the control, T2DM, DV, T2DM+AG490 and DV+AG490 groups. Chemotaxis of treated HUVECs toward THP-1 cells was assessed using Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In contrast to markers of inflammation, miR-181b levels did not correlate with blood glucose or HbA1c in our cohort. Although we and Sun et al [28] found that miR-181b expression in HMEC-1 and human umbilical vein endothelial cells (HUVEC) is reduced by high glucose concentrations, Yang et al [37] reported activation of the miR-181a/b-specific transcription factor signal transducer and activator of transcription (STAT) 3 in HUVEC treated with sera from diabetics pointing to a more complex regulation of miR-181b expression in humans. This may explain why the miR-181b expression in our healthy controls did not differ from those in poorly controlled diabetes (Additional file 6: Figure S5A).…”
Section: Low Mir-181b: Association With a Pro-thrombotic And Pro-inflmentioning
confidence: 65%
“…In contrast to markers of inflammation, miR-181b levels did not correlate with blood glucose or HbA1c in our cohort. Although we and Sun et al [28] found that miR-181b expression in HMEC-1 and human umbilical vein endothelial cells (HUVEC) is reduced by high glucose concentrations, Yang et al [37] reported activation of the miR-181a/b-specific transcription factor signal transducer and activator of transcription (STAT) 3 in HUVEC treated with sera from diabetics pointing to a more complex regulation of miR-181b expression in humans. This may explain why the miR-181b expression in our healthy controls did not differ from those in poorly controlled diabetes (Additional file 6: Figure S5A).…”
Section: Low Mir-181b: Association With a Pro-thrombotic And Pro-inflmentioning
confidence: 65%
“…The SOCS family of endogenous regulators sits at the crossroad of multiple signaling mechanisms, making them attractive targets for the treatment of inflammatory diseases [18,19]. In diabetes-mediated pathologies, alterations of SOCS1 expression associate with cardiovascular risk and progressive renal disease in patients [32,33]. Animal studies performed by a number of groups, including ours, have shown convincingly that SOCS1 gene absence, leading to sustained STAT activation, aggravates immune and inflammatory responses [23,25,34,35].…”
Section: Discussionmentioning
confidence: 88%
“…In agreement with these findings, we unveil that METTL3 maintains pluripotency of piPSCs by sustaining JAK2 expression, inhibiting SOCS3 expression and activating STAT3/KLF4/SOX2 signal axis. The JAK2–STAT3 pathway plays important roles in a variety of biological processes, and dysfunctional JAK2–STAT3 pathway may contribute to diseases such as cancer, heart disease and obesity 3537 . The regulation of JAK2–STAT3 signal pathway by m 6 A methylation could be a common mechanism that affects a range of other biological processes, which should be further investigated.…”
Section: Discussionmentioning
confidence: 99%